2013
DOI: 10.1371/journal.pgen.1003268
|View full text |Cite
|
Sign up to set email alerts
|

Retroactive Maintains Cuticle Integrity by Promoting the Trafficking of Knickkopf into the Procuticle of Tribolium castaneum

Abstract: Molting, or the replacement of the old exoskeleton with a new cuticle, is a complex developmental process that all insects must undergo to allow unhindered growth and development. Prior to each molt, the developing new cuticle must resist the actions of potent chitinolytic enzymes that degrade the overlying old cuticle. We recently disproved the classical dogma that a physical barrier prevents chitinases from accessing the new cuticle and showed that the chitin-binding protein Knickkopf (Knk) protects the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…8). All insects establish compact and structured exoskeletal cuticles at their outermost body parts (4,29,32,33,36,37). Our data argue that structural similarities of the body wall cuticle and molecular conservation of involved proteins (8, 9, 15-19, 38 -40) point toward a highly conserved mechanism of procuticle formation among chitinous invertebrates.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…8). All insects establish compact and structured exoskeletal cuticles at their outermost body parts (4,29,32,33,36,37). Our data argue that structural similarities of the body wall cuticle and molecular conservation of involved proteins (8, 9, 15-19, 38 -40) point toward a highly conserved mechanism of procuticle formation among chitinous invertebrates.…”
Section: Discussionmentioning
confidence: 70%
“…This suggests that chitin matrix protection must be affected. Our findings may not exclude other potential protective proteins (32), and yet uncharacterized Drosophila Knk-like proteins (33) could depend on Obst-A. However, the wrinkled cuticle specifically observed in obst-A null and transheterozygous obst-A;knk mutants and the localization of Obst-A and Knk proteins in the outer cuticle led to the speculative hypothesis that they act in cuticle stability of the newly synthesized and packaged chitin matrix.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These are primarily endochitinases that randomly cleave chitin present in the cuticle to chitooligosaccharides that are further hydrolyzed by exoenzymes to N-acetyl-glucosamine monomer, which is reused to synthesize a new cuticle (Chaudhari et al 2013). Chitinases from Bombyx mori, Manduca sexta have been extensively studied.…”
Section: Chitinase Sourcesmentioning
confidence: 99%
“…Naked chitin fibers need to interact with chitinbinding protein to stabilize the helicoidal layers of cuticle (Rebers and Riddiford 1988;Rebers and Willis 2001;Merzendorfer and Zimoch 2003;Moussian 2010). The largest member of these chitin-binding proteins is the CPR family, which may contribute to coordinating the interactions between chitin and the proteinaceous matrix (Rebers and Riddiford 1988;Rebers and Willis 2001;Togawa et al 2004;Magkrioti et al 2004;Willis 2010;Andersen 2011), and RR-type chitin-binding protein, chitin, and chitinase are colocalized in the procuticle (Moussian et al 2006;Chaudhari et al 2011Chaudhari et al , 2013Arakane et al 2012). The recent study on Tribolium castaneum indicated that the TcCPR4 (a RR1-type cuticular protein) distribute the region nearby chitin laminae and can affect the chitin content (Arakane 2013).…”
Section: Bmorcpr2 Affects Cuticle Chitin Content and Larval Molting Vmentioning
confidence: 99%